How Tax Knowledge Mediates Business Performance? - Mangoting, Yenni; Leoni, Michelle; Natalia, Celine (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2024)
This study aimed to determine the influence of tax awareness on business performance and to examine the effect of tax knowledge as a mediating variable. The research adopted a survey with the distribution of questionnaires via G-Forms. The sample consisted of individual taxpayers who own sole proprietorships. The study demonstrated that high tax awareness and knowledge positively impacted taxpayers to fulfill their tax obligations, thereby enhancing business performance. The results of the mediation test confirmed that tax knowledge plays an effective mediating role. Tax awareness remained the main factor. Increasing tax awareness encourages taxpayers to seek broader knowledge about tax regulations and their interpretations, which affects the efficiency of the company’s cash flow. This drives companies to make innovative decisions by optimizing tax regulations and incentives. This study confirmed that tax awareness and tax knowledge contributed to improving taxpayers’ compliance. Nevertheless, integrating tax awareness with tax knowledge not only improves taxpayers’ compliance but also leads to improved business performance.